Strukturudvikling i pelsdyravlen: Kan udviklingen FORKLARES OG FORUDSIGES? - Lawson, L.; Hansen, H. (Tidsskrift for Landøkonomi, 2024)
Strukturudvikling i pelsdyravlen: Kan udviklingen FORKLARES OG FORUDSIGES?